Palm Leaf as a Thermal Insulation Material - AL-Nesearawi, M. A.-N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This paper presents calculat,ion of thermal conductivity (K) of palmleaf  experimentally  using  Lee s  disc  method   to  be  used  as   thermalinsulator. The therma l conducti vity is found to be equal to (k=0.03W/mK)indicating  that  palm l eaf is a good thermal  insulator com pared to the other insulators. The effect of the thermal insulator   thickness  on temperature di lTt::rence,  heat   transfer    coefficient,   thermal     conductance,   thermal resistance,  thermal  insulation are in vestigated in this paper. It was  found that i ncreasi ng thickness of the good i nsulator (such as palm !eat)  leads to increasing both thermal resistance and insulation  while  decreasing both heat transfer  coefficient  and thermal conductance  until specific point wh ich after it they are not affected by thickness (they being constant).